Naskah Pembagian Kekuasaan dalam Negara: Edisi Teks dan Kritik Teks - Nelvi Susanti; Nurul 'Afifah; Ahmad Taufik Hidayat; Yulfira Riza (Universitas Sebelas Maret, 2024)
Pembahagian Kekuasaan dalam Negara (PKDN) wich translated into The Division of State Power, is a manuscript that discusses political issues. including legislative power organized by the House of Representative Council or the National Assembly, the executive wich held by the president or cabinet, and the judicial power. This research is a qualitative study in the field of philology. The focus of this research is the manuscript of the Division of Power in the State (PKDN) written by H. Burhnuddin Syarif. This manuscript was discovered in the Research and Development Center for Lectures and Religious Treasures of Indonesian Ministry of Religion with collection code: LKK_SUMBAR2014_MUNGKA 003. This purpose of this study is to discuss the editing and critical examination of the texts using standard editions methods to obtain a manuscript free from copy errors, as well as to describe text changes and examine copy errors found in PKDN manuscripts. The results showed in the PKDN manuscript there are two errors in the form of omission and addition. This omission error is the lack of letters in a sentence, while the addition error is the excess of letters in several sentences in this manuscript.